AWARENESS AND USE OF THE ADULT PRE-EXERCISE SCREENING SYSTEM (APSS) IN THE AUSTRALIAN FITNESS INDUSTRY. Issue 7 (11th March 2014) - Perera, N; Keyzer, P; Dietrich, J; Norton, K; Sekendiz, B; Jones, V; Coyle, I; Finch, C
Abstract : Background: The Australian Adult Pre-Exercise Screening System (APSS) was developed as the national standard to promote quality control, consistency of practices across the industry and use of pre-exercise screening as a risk management tool to identify and manage health and injury risks associated with fitness activities. Stage 1 of APSS is compulsory and aims to identify those at high-risk of cardiovascular, metabolic or respiratory diseases and refer to medical/allied health professionals for clearance. Stage 2 and 3 are optional and screen for moderate or low risk individuals. Objective: To evaluate awareness and use of the APSS across the Australia-wide fitness industry. Design: A nationwide online self-report survey completed by fitness professionals. Setting: Australia-wide Fitness Industry using snowball sampling. Participants: 1178 adults, who own, manage or work in a registered/unregistered fitness business. Main outcome measurements: 1) Awareness and frequency of use of APSS, and 2) frequency of pre-exercise screening of any form and satisfaction of the pre-exercise screening being used. Results: 24% of respondents were insufficiently aware of the APSS, 47% aware and 29% were fully aware of APSS. Only 20% of respondents used APSS extremely frequently, 35% used APSS frequently and 45% used APSS infrequently. 65% of survey respondents always conducted a pre-exercise screening with their clients. 66% believed that their pre-exercise medical screenings of customers were good; 22% reported extremely good and 12% reported it was poor. Chi-squared tests identified significant relationships between conducting any pre-exercise screening and frequency of use of APSS (P<.001), satisfaction of pre-exercise screening and frequency of APSS use (P<.001), and awareness of APSS and the frequency of its use (P<.001). Conclusions: Frequency of use of APSS as a risk management tool by fitness professionals is strongly correlated with their awareness of it, their level of satisfaction of pre-exercising screening being used.